PELAKSANAAN MEDIASI DALAM PENYELESAIAN SENGKETA PERCERAIAN OLEH BADAN PENASEHAT PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) KOTA PEKANBARU - Ardya Englando Baker; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Divorcement is a defeasance of a matrimony through a verdict or an indictment of one of thecouples in the marriage. According to the article 38 of Marriage Act that a divorcement is a“breakup of marriage”. Pekanbaru is one of the municipalities in Indonesia that has an increasingnumber of divorces. One of peaceful efforts is able to overcome a divorce case is a mediationprocess. The Board of Advisor, Coaching, and Preservation of Marriage (Badan Penasehat,Pembinaan, dan Pelestarian Perkawinan, BP4) in the city possesses tasks to handle marriageproblems where one of its duties is to protect a marriage divorce through a mediation process.However, based on the existing data, the total divorces registered in the Religious Court ofPekanbaru City is numerously and inversely proportional with the total of cases registered in theBP4 of the city. The purposes of this undergraduate thesis were (1) to seek the mediation process inovercoming the divorce disputes conducted by BP4 of Pekanbaru city, and (2) to find out ways ofthe board in order to carry out the mediation process of divorce disputes effectively.This study is able to be categorized into a sociological research due to it had been takendirectly in the research location. It was conducted in the BP4 of Pekanbaru City. Population andsamples of this research were all parties related to the observed problems. Data came from threesources, primary, secondary and tertiary. Data were collected by interviews and literature studies.This research infers two main findings. First, a mediation process in the BP4 of PekanbaruCity consists of five steps such as registration, determining mediator, call related parties, mediationtrial, and result of mediation. In implementing those steps, there are some finding obstacles namelyinternal factors likes a lack of mediator officers and a difficulty to unify both parties, and externalfactors such as an absence of mediation room and nonappearance of a special regulation inorganizing mediation process in the board. Second, efforts ought to be carried out for implementingthe mediation process in the board effectively through two ways, internally and externally.Internally, numbers of mediators have to be added and their capabilities should be upgraded.Externally, a mediation room is a must and the special acts to arrange the mediation process in theboard is highly recommended.Keywords: divorcement – BP4 – mediation